Emotion regulation and disordered eating: The distinct effects of body image-related cognitive fusion and body appreciation - Bento, S. (2017)
Different emotion regulation processes may influence the impact of a negative perception of one’s own weight and body image on the engagement in disordered eating. In this regard, the present study aims to clarify the distinct effects of cognitive fusion and body appreciation in the relationship between body image discrepancy and disordered eating, while controlling the effect of BMI, in a sample of 369 women. Results indicated that women who perceived their body as significantly discrepant from the socially idealized thin figure show greater tendency to engage in disordered eating behaviours. Notwithstanding this direct association, the impact of negative body image evaluation in disordered eating seems to be partially carried by higher body image-related cognitive fusion and lower body appreciation. Furthermore, results offer relevant contributions by providing empirical support for the importance of targeting and cultivating cognitive defusion and self-compassionate attitudes as protective emotion regulation strategies against eating psychopathology.